A Systematic Literature Review of Ethnomathematics-Based Card Games in Mathematics Learning - Evi Yunia Nugraheni; Sri Subanti; Triyanto (Universitas Veteran Bangun Nusantara, 2026)
Ethnomathematics-based card games are a mathematics learning innovation that integrates local cultural elements to create contextual and meaningful learning experiences. However, previous research is limited and has not comprehensively mapped the integration between game design, cultural context, and mathematical abilities through a Systematic Literature Review (SLR) approach. This study aims to describe game design, gameplay, regional culture, materials, educational level, and mathematical abilities developed through ethnomathematics-based card games. This study used a Systematic Literature Review approach with the PRISMA protocol. A Google Scholar search yielded 636 initial articles, which were then selected based on inclusion and quality criteria, resulting in 13 articles for analysis. The results indicate that card games, developed in both analog and digital formats, incorporate cultural contexts such as traditional games, local food, cultural motifs, and traditional houses, and are predominantly used in elementary and junior high schools. The use of this medium contributes to improving students' conceptual understanding, numeracy skills, problem-solving skills, and learning motivation. This study provides a comprehensive synthesis of the design, implementation, and impact of ethnomathematics-based card media as a basis for developing innovative and contextual mathematics learning.